2019
DOI: 10.1038/s41598-018-36968-y
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Case-Control Study on the Association Between Colds, Depressive Symptoms during Pregnancy and Congenital Heart Disease in Northwestern China

Abstract: The purpose of this study was to explore the association between colds, depressive symptoms during pregnancy and offspring congenital heart disease (CHD). A 1:2 matching case-control study was conducted in Northwest China. Information was gathered by a structured questionnaire and was reviewed by investigators on the spot. Multivariate logistic regressions and nonlinear mixed effect model were performed. 614 cases and 1228 controls were available in this study. After adjusting for potential confounders, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…exposed group is inconsistent with our interest (n = 12) Finally, we identified 16 eligible articles [ 18 22 , 28 38 ] in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…exposed group is inconsistent with our interest (n = 12) Finally, we identified 16 eligible articles [ 18 22 , 28 38 ] in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A Chinese case-control study found that prenatal depressive symptoms had signi cantly increased OR (1.94) for CHD. However, the symptoms were evaluated using the Zung Self-Rating Depression Scale after birth, leading to recall bias [12]. Meanwhile, in the UK cohort, diagnosis of depression without antidepressant use during the rst trimester had no signi cant OR (1.10).…”
Section: Discussionmentioning
confidence: 99%
“…A lower socioeconomic status is associated with common mental disorders [9,10], and the association between anti-depressant use during pregnancy and CHD has been reported in a meta-analysis [11]. Concerning actual depressive symptoms, a case-control study in China reported that depressive symptoms during pregnancy were related to a signi cantly increased odds ratio (OR) for infant CHDs [12]. However, the diagnosis of depression in a UK cohort and depressive symptoms in a Northern Ireland case-control study was not related to infant CHDs [8,13].Thus, whether maternal psychological distress, including depressive symptoms, is a risk factor for CHD has not been fully investigated, and there have been no reports on the combined effects of maternal education, income, and maternal psychological distress on CHD.…”
mentioning
confidence: 99%
“…Therefore, we hypothesized that the relationship between maternal lifestyle during pregnancy and CHD varied significantly from region to region in Shaanxi. In most previous studies, however, conventional regression models were used to produce average parameters to explore the relationship between maternal lifestyle during pregnancy and CHD over the whole study area, but spatial heterogeneity was neglected 17 20 . In the present study, we used the Geographically Weighted Logistic Regression (GWLR) model to generate local coefficients to account for geographical variations in evaluating the correlation between CHD in infants and maternal lifestyles during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Other socio-demographic factors included fetal gender (male, female), fetal number (singleton, twin and multi-fetal), infant parity (1, 2, or ≥ 3), childbearing age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), ≥ 30 years), mother's education (primary school and below, junior high school, senior high school, college and above), mother's marriage (first marriage, others), household registration (urban, rural), Household wealth Index (poor, middle-income, rich), altitude of residence (< 500, 500-1000, > 1000), mother's residence during pregnancy (floating, permanent), family history of CHD (no , yes), and area (South Shaanxi, Central Shaanxi, North Shaanxi). Household wealth index based on the principal component analysis was used to assess the household economic level of the participants.…”
mentioning
confidence: 99%